The Role of the Cost Method Based on Specifications in Supporting the Competitiveness of the Industrial Sector of Poultry Companies' A Field Study on Arab Poultry Company-Khartoum - Balola, Yasir Musa; Hamed, Mahgoub Abdalla (Journal of Economic, Administrative and Legal Sciences, 2021)
The aim of the research is to identify the cost method based on specifications and to indicate its role in supporting competitiveness. The descriptive analytical approach was used to achieve the research objectives. Use the questionnaire to collect data from the Arab Poultry Company. Several results were reached, including the application of the cost method. On the basis of specifications in the Arab Poultry Company, a product with high reliability and durability, more flexible and in response to changes in consumer tastes, which led to the attractiveness of the product and then achieving the objectives of the economic untitled to raise the efficiency of their competitiveness. One of the recommendations is to conduct more scientific studies in the future in other sectors concerned with modern methods of management accounting in light of the highly competitive business environment.
Keywords: cost based on specifications; competitiveness; industrial sector; Khartoum